(untitled) (Research, Society and Development, 2020)
Welcoming people with Autistic Spectrum Disorder (ASD) has been a challenge for nursing teams, as autism is still a topic that requires relevance. This study aims to: identify the importance of the nursing team when treating a person with ASD, present the characteristics of the person with ASD that should be recognized by the nursing team and describe how the approach to patients with ASD occurs. It is a literature review that followed the following steps: establishment of the hypothesis and objectives of the literature review, establishment of inclusion and exclusion criteria for articles. They were selected in the period from March 2020. A 5-year time frame was established, with the intention of mapping the development process of the most recent publications on the theme in the country, and the following national research databases were used. Virtual Health Library (VHL). From the verification of the articles, it was noticed that there is little incidence of articles aimed at nursing care / care for people with ASD, and that most articles report the disorder itself and its characteristics, and not specifically the assistance / care needed. It is up to the nurse, the competence to invest in her work team, in continuing education in relation to people with ASD, thus demonstrating to the family that the team knows how to deal with their relative with ASD, who are among us and in need of an effective reception.